A unique arginine cluster in PolDIP2 enhances nucleotide binding and DNA synthesis by PrimPol. Issue 4 (3rd February 2021) - Kasho, Kazutoshi; Stojkovič, Gorazd; Velázquez-Ruiz, Cristina; Martínez-Jiménez, Maria Isabel; Doimo, Mara; Laurent, Timothée; Berner, Andreas; Pérez-Rivera, Aldo E; Jenninger, Louise; Blanco, Luis; Wanrooij, Sjoerd
Abstract: Replication forks often stall at damaged DNA. To overcome these obstructions and complete the DNA duplication in a timely fashion, replication can be restarted downstream of the DNA lesion. In mammalian cells, this repriming of replication can be achieved through the activities of primase and polymerase PrimPol. PrimPol is stimulated in DNA synthesis through interaction with PolDIP2, however the exact mechanism of this PolDIP2-dependent stimulation is still unclear. Here, we show that PrimPol uses a flexible loop to interact with the C-terminal ApaG-like domain of PolDIP2, and that this contact is essential for PrimPol's enhanced processivity. PolDIP2 increases primer-template and dNTP binding affinities of PrimPol, which concomitantly enhances its nucleotide incorporation efficiency. This stimulation is dependent on a unique arginine cluster in PolDIP2. Since the polymerase activity of PrimPol alone is very limited, this mechanism, where the affinity for dNTPs gets increased by PolDIP2 binding, might be critical for the in vivo function of PrimPol in tolerating DNA lesions at physiological nucleotide concentrations.